Frequency of Perceived Fear of Vitamin D Deficiency among Female Medical Students and its Relationship with Dietary Practices - Sana Noor, Noor Shahid, Uzair Azhar, Faryal Arif, Suhla Azhar, Aneeqa Ravail, (Pakistan Journal of Medical & Health Sciences, 2023)
Objectives: To determine the precautionary measures and determinants leading to the fear of vitamin D deficiency among female medical students in Lahore. Methodology: A cross-sectional study was carried out among medical students in Lahore from December 2021 to March 2022. The data was collected from 383 female medical students using the non-probability convenience sampling technique. The data was collected from a self-designed questionnaire to collect information about the vitamin D deficiency. Results: The average age of the participants was 21.21±1.40 SD. Most of the participants were unmarried. Nearly 31 (8.1%) were married. The knowledge of Vitamin D deficiency was statistically insignificantly different among different socio-economic class and smoking status (p-value = 0.30, p-value = 0.68). Conclusion: The fear of Vitamin D deficiency was significantly associated with past family history of bone disorder. Most of the participants who had feared of Vitamin D deficiency reported that they do not have any kidney and liver disorder. Polycystic ovary disorder was statistically significantly related with fear of Vitamin D deficiency. Gastrointestinal disorder was significantly associated with Vitamin D deficiency fear. Keywords: Vitamin D deficiency, Physical Inactivity, Diet